Street art from around the world - Hunter, Garry; Arcturus (Cargo ship) (London : Arcturus, 2012)
"Our towns and cities are saturated with the imagery of commerce and advertising, but alongside it a new creative phenomenon is demanding our attention: art, on the street, available for everyone to see. Banksy, Blek le Rat, Os Gemeos and JR are just some of the major practitioners whose works are showcased in this book. From huge murals to exquisite miniature art that can easily be missed, the examples here are powerful expressions of what it is to be a modern human living in an urban landscape." --Back cover.
Keywords: Street art